Harmonic Univalent Functions Defined by Post Quantum Calculus Operators - (:unkn) unknown (SCIENDO, DE GRUYTER POLAND SP Z O O, BOGUMILA ZUGA 32A STR, 01-811 WARSAW, POLAND, 2019)
We study a family of harmonic univalent functions in the open unit disc defined by using post quantum calculus operators. We first obtained a coefficient characterization of these functions. Using this, coefficients estimates, distortion and covering theorems were also obtained. The extreme points of the family and a radius result were also obtained. The results obtained include several known results as special cases.
Keywords: (p, q)-calculus; q-calculus; (p, q)-Salagean Harmonic Function; Salagean Differential Operator